2015
DOI: 10.1007/s00345-015-1526-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the efficacy and safety between robotic-assisted versus open pyeloplasty in children: a systemic review and meta-analysis

Abstract: Robotic-assisted pyeloplasty may be a promising alternative minimal invasive surgery for UPJO in children if the higher complication rates and higher costs in the RP can be overcome in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…[40–42] During the past 5 years, many authors from established general thoracic centers reported studies that supported the feasibility, reproducibility, effectiveness, and safety of the robotic-assisted procedures compared with the open thymectomy. [24,3136] To the best of our knowledge, this is the first meta-analysis comparing these 2 surgical techniques of thymectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[40–42] During the past 5 years, many authors from established general thoracic centers reported studies that supported the feasibility, reproducibility, effectiveness, and safety of the robotic-assisted procedures compared with the open thymectomy. [24,3136] To the best of our knowledge, this is the first meta-analysis comparing these 2 surgical techniques of thymectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of choice is surgery in case of flank pain, loss of DRF, or relevant obstruction in dynamic renal scans. The dismembered pyeloplasty (DMP) is the gold standard to successfully treat both intrinsic and extrinsic UPJO in children; recently published reports proved comparable results for laparoscopic, one trocar-assisted, or robotic-assisted dismembered pyeloplasty (LDMP, OTAP, RDMP), even in small infants [9,10]. Furthermore, in adults, nondismembered pyeloplasty…”
Section: Introductionmentioning
confidence: 94%
“…The post-operative success rate was comparable in the 2 groups, but there was a significantly higher complication rate and higher costs in the robotic group. 38 Additionally, it has been shown that with 2 years of follow-up, only 5% of patients who underwent robotic pyeloplasty require a secondary procedure, compared with 13% of those who underwent a standard laparoscopic pyeloplasty. 39 Moreover, robot-assisted laparoscopic reoperative repair after failed primary treatment is safe and effective, and is less technically demanding than open repair for UPJO.…”
Section: Robot-assisted Pyeloplastymentioning
confidence: 99%